2022
DOI: 10.3390/ijms23042299
|View full text |Cite
|
Sign up to set email alerts
|

The Potential to Fight Obesity with Adipogenesis Modulating Compounds

Abstract: Obesity is an increasingly severe public health problem, which brings huge social and economic burdens. Increased body adiposity in obesity is not only tightly associated with type 2 diabetes, but also significantly increases the risks of other chronic diseases including cardiovascular diseases, fatty liver diseases and cancers. Adipogenesis describes the process of the differentiation and maturation of adipocytes, which accumulate in distributed adipose tissue at various sites in the body. The major functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 155 publications
0
24
0
Order By: Relevance
“…Although large, the repertoire of genes, proteins, molecules, or even metabolic pathways presents a lack of knowledge about their interactions and specific functions during adipogenesis and processes associated with obesity. Moreover, the complex redundancy of these players makes it difficult to establish reliable markers for obesity and related metabolic diseases [ 5 , 143 ]. Still, although studies point to a possible link between obesity and different markers, it is not clear whether these markers, once altered, lead to obesity or whether the onset of obesity is the trigger for the differential expression of these markers.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…Although large, the repertoire of genes, proteins, molecules, or even metabolic pathways presents a lack of knowledge about their interactions and specific functions during adipogenesis and processes associated with obesity. Moreover, the complex redundancy of these players makes it difficult to establish reliable markers for obesity and related metabolic diseases [ 5 , 143 ]. Still, although studies point to a possible link between obesity and different markers, it is not clear whether these markers, once altered, lead to obesity or whether the onset of obesity is the trigger for the differential expression of these markers.…”
Section: Challenges and Limitationsmentioning
confidence: 99%
“…4 Therefore, the study of liver and adipose lipid metabolism is of great value in alleviating metabolic diseases. 5 The umami taste receptor T1R1/T1R3, a G protein-coupled receptor formed by heterodimerization of T1R1 and T1R3 (both of which belong to the T1R class), has been reported to be a chemoreceptor for a variety of amino acids, especially Lglutamate. 6,7 Recently, studies have found that T1R1/T1R3 mediates the regulation of amino acid metabolism in multiple tissues and organs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Generally, obesity is mainly caused by disordered lipid metabolism and excessive lipid deposition in the liver and adipose tissues . Therefore, the study of liver and adipose lipid metabolism is of great value in alleviating metabolic diseases …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, considering the complexity of mechanistic and functional aspects of adipose tissues, as well as the different epigenetics changes and signaling pathways that can modulate specific obesity-associated genes, researchers have also paid their attention to the search of natural or synthetic compounds or biologic molecules acting at this level [ 26 ]. Indeed, the identification of targeted drugs regulating signaling and epigenetic status in adipogenesis could shed light on the treatment of obesity or related metabolic diseases through modulating adipogenesis [ 26 ].…”
mentioning
confidence: 99%
“…On the other hand, considering the complexity of mechanistic and functional aspects of adipose tissues, as well as the different epigenetics changes and signaling pathways that can modulate specific obesity-associated genes, researchers have also paid their attention to the search of natural or synthetic compounds or biologic molecules acting at this level [ 26 ]. Indeed, the identification of targeted drugs regulating signaling and epigenetic status in adipogenesis could shed light on the treatment of obesity or related metabolic diseases through modulating adipogenesis [ 26 ]. Potential candidates in this direction seem to be epigenetic modulators affecting histone acetylation such as C646, a specific CBP/p300 inhibitor that significantly decreased the adiposity in larval zebrafish [ 27 ], or histone deacetylase inhibitors that reduced lipid accumulation in cultured adipocytes [ 28 ] and caused loss of body weight [ 29 ].…”
mentioning
confidence: 99%